Harsh occupations, life expectancy and social security - Pestieau, Pierre; Racionero, Maria (Camberra, 2013)
"Should special pension provisions be offered to workers in harsh occupations? We address this question in an optimal tax setting where individuals differ in longevity and occupation. Longevity is private information but workers in harsh occupations have on average shorter lifes than workers in safe occupations. We adopt a weighted utilitarian social objective to partially redress the implicit redistribution from short- to long-lived individuals that the unweighted utilitarian objective entails. We show that there is a case for differentiating the social security policy by occupation. We also show that short-lived workers are induced to overconsume when young and to retire early in order to prevent mimicking by long-lived ones. This is achieved by taxing, often quite heavily, the savings and the earnings from prolonging activity of short-lived individuals."